"Health, wealth and achievements of former very premature infants in adult life". Issue 3 (June 2020) - Saigal, Saroj; Morrison, Katherine; Schmidt, Louis A.
Abstract: Very preterm survivors born in the early neonatal intensive care era are now in their middle adulthood. The literature from cohort studies and population-linked registries indicate that extreme prematurity is associated with lower educational attainment and income, higher need for social assistance, and lower rates of marriage/partnership and reproduction. In addition, with increasing age, many general and system-specific adverse health outcomes, such as psychiatric problems, hypertension, and cardio-metabolic disorders have emerged, resulting in high cumulative health care costs across the life-span. Yet, a significant majority of adults born preterm are leading productive lives and contributing to society. Although this information may not be directly applicable to survivors of modern neonatal intensive care, there is much to learn from these findings to inform and guide us into designing effective strategies to improve the health and well-being of future very premature infants. The longer-term outcome of more recent survivors remains to be determined.